P147 IS HYBRID MINIMALLY INVASIVE ESOPHAGECTOMY SAFE FOR SIEWERT TYPE II OESOGASTRIC JUNCTION TUMORS?. (23rd November 2019) - Simon, Gabriel; Alexandre, Challine; Marguerite, Messier; Clarisse, Eveno; Maxime, Warlaumont; Guillaume, Piessen
Abstract: Background: In the MIRO trial, hybrid minimally invasive Ivor Lewis (IL) resulted in a lower incidence of intraoperative and postoperative major complications, specifically pulmonary complications, than open IL without compromising oncological resection criteria and 3 years survival results. However, only infracarenal and Siewert I oesogastric junction (OGJ) tumors were included. Whether hybrid approach for Siewert II OGJ tumours remains unknown with a potential risk of tumor spillage. The aim of this study was to compare hybrid and open IL for patients with Siewert II OGJ tumours. Materials and Methods: Data from 83 patients who underwent surgery for Siewert II OGJ tumours in our institution were collected prospectively between 2011 and 2017. Overall, 53 patients were included in the hybrid group and 30 in the open group. The main outcome was radicality of resection (R0 / R1 margins and number of lymph nodes resected). Groups were compared in univariate and multivariate analysis with a propensity score-adjustment. Results: After adjustment, the hybrid and open groups were comparable in terms of number of lymph nodes resection: OR=0.65 (0.25-1.66) and radicality of resection; (R0/R1): OR=0.93 (0.10-8.58) with similar long term overall (OS) and disease-free (DFS) survival (5-year OS: 68% vs. 58%, p=0.463; 5-year DFS: 56% vs. 42%, p=0. 323). There were significantly fewer pulmonary complications in the hybrid group: OR=0.38 (.14-0.95). Conclusion: Hybrid IL for Siewert II OGJ tumors do not compromise oncological quality resection and long term OS and DFS and results in a lower incidence of pulmonary complications than open IL.